2017
DOI: 10.3389/fpsyg.2017.01029
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Social Play for Children with PDDs: Effects of Paired Robotic Devices

Abstract: Interacting with toys and other people is fundamental for developing social communication skills. However, children with autism spectrum disorder (ASD) are characterized by having a significant impairment in social interaction, which often leads to deficits in play skills. For this reason, methods of teaching play skills to young children with ASD have been well documented. Although previous studies have examined a variety of instructional strategies for teaching skills, few studies have evaluated the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…On the contrary, this phenomenon does not occur in people who are within the autistic spectrum. Unlike children with typical development, children with ASD are often more involved with their thoughts and feelings than with other people (Carrasco, Alarcón & Trianes, 2018;Charman, 2003;Matsuda, Nunez, Hirokawa, Yamamoto & Suzuki, 2017).…”
Section: Why Is It Important To Develop Joint-attention In Children With Asd?mentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, this phenomenon does not occur in people who are within the autistic spectrum. Unlike children with typical development, children with ASD are often more involved with their thoughts and feelings than with other people (Carrasco, Alarcón & Trianes, 2018;Charman, 2003;Matsuda, Nunez, Hirokawa, Yamamoto & Suzuki, 2017).…”
Section: Why Is It Important To Develop Joint-attention In Children With Asd?mentioning
confidence: 99%
“…This ability allows us to cooperate and socialize with others. Interacting with other children during childhood is fundamental to developing the social and language skills we need in adulthood (Matsuda et al, 2017).…”
Section: Why Is It Important To Develop Joint-attention In Children With Asd?mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the effect of the intervention with COLOLO on children's play and social behavior has already been investigated using a psychological approach [37]. We compared the effect of COLOLO's visual feedback condition against no-feedback condition and found that visual feedback was related with an increased number of contact with toys and an increased number of gaze shifting toward the therapist's toy.…”
Section: Proposal and Contributionmentioning
confidence: 99%
“…To facilitate the number of turn-taking instances during the sessions with COLOLO, both increasing the number of successful attempts of turn-taking and reducing the failed attempts are important aspects. We hypothesized that more colored-lights feedback would elicit more manipulation (H1) based on the insights from our previous study [37]. However, in the sessions with one-sided lighting, the participants manipulated the device as much as they did during the sessions with two-sided lighting.…”
Section: Effects Of Sensory Feedback On Turn-taking Behaviorsmentioning
confidence: 99%